2022
DOI: 10.3390/cancers14215463
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery after Uterine Corpus Cancer Surgery: A 10 Year Retrospective Cohort Study of Robotic Surgery in an NHS Cancer Centre

Abstract: Royal Surrey NHS Foundation Trust introduced robotic surgery for uterine corpus cancer in 2010 to support increased access to minimally invasive surgery, a central element of an enhanced recovery after surgery (ERAS) pathway. More than 1750 gynaecological oncology robotic procedures have now been performed at Royal Surrey NHS Foundation Trust. A retrospective cohort study was performed of patients undergoing surgery for uterine corpus cancer between the 1 January 2010 and the 31 December 2019 to evaluate its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Our future aim is to further investigate the influence of distinct parts of RAL surgery performed by a trainee on peri-operative and survival outcomes. Furthermore, compared to other robotic cohorts [28][29][30] we have a high percentage of high grade tumours (44.9%) and high stage disease (31.1%) which is related to the tertiary referral status of our department. This might limit the generalisability of our results.…”
Section: Strengths and Limitationsmentioning
confidence: 79%
“…Our future aim is to further investigate the influence of distinct parts of RAL surgery performed by a trainee on peri-operative and survival outcomes. Furthermore, compared to other robotic cohorts [28][29][30] we have a high percentage of high grade tumours (44.9%) and high stage disease (31.1%) which is related to the tertiary referral status of our department. This might limit the generalisability of our results.…”
Section: Strengths and Limitationsmentioning
confidence: 79%
“…Therefore, previous studies on surgical outcomes in endometrial cancer have performed case-matching based on BMI ( 36 ). On the other hand, a recent study by Uwins et al ( 34 ) on surgical outcomes of robotic surgery for endometrial cancer did not perform matching on BMI and found no negative influence of BMI on hospital stay and conversion rate. In our study BMI differed significantly between training and non-training cases and this might have been a confounding factor for intra- and post-operative outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…One study ( 32 ) observed less estimated blood loss in cases performed early in the learning curve compared to later cases, which was also observed in our cohort. BMI is a possible confounder of EBL, with more blood loss and more blood transfusions in higher BMI groups ( 34 ). Since BMI was significantly higher in non-training cases, this is another possible explanation for the significant difference in EBL although no difference in blood transfusion rates was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation